Changes in night sky brightness after a countywide LED retrofit. (15th August 2021) - Hung, Li-Wei; Anderson, Sharolyn J.; Pipkin, Ashley; Fristrup, Kurt
Abstract: The US National Park Service (NPS) Night Skies Program measured changes in sky brightness resulting from a countywide lighting retrofit project. The retrofit took place in Chelan County, a gateway community to North Cascades National Park and Lake Chelan National Recreation Area in Washington State. The county retrofitted all 3693 county-owned high pressure sodium (HPS) street lamps to full cutoff LEDs. This number is about 60% of the County's total outdoor street and area lights. About 80% of the newly installed lights were 3000 K in color temperature and 20% were 4000 K. The 4000 K LEDs were used to meet Washington State Department of Transportation guidelines. To measure sky brightness, we used the NPS night sky camera system before the retrofit started in 2018 and after its completion in 2019. These images were photometrically calibrated and mosaicked together to provide hemispherical images in V band. For comparison with our ground-based measurement, we obtained the satellite imagery taken by Visible Infrared Imaging Radiometer Suite (VIIRS) onboard the Suomi National Polar-orbiting Partnership satellite. Our measurements show that the post-retrofit skyglow became brighter and extended higher in the sky, but upward radiance, as measured by the day-night band radiometer, decreased. These divergent results are likely explained by a substantial increase in light emitted at wavelengths shorter than 500 nm, and a relative decrease in upward light emission due to better shielded luminaires. These results also demonstrate that earlier models relating VIIRS day-night band data to skyglow will – at a minimum – require substantial revision to account for the different characteristics of solid state luminaires. Highlights: The skyglow became brighter after the countywide LED lighting retrofit. Chelan County retrofitted 3693 high pressure sodium (HPS) streetlights to LEDs. The VIIRS satellite failed to detect the increase of upward radiance in this case. Earlier models relating VIIRS data to LED skyglow will require substantial revision. Typical one-for-one HPS to LED replacements are likely to increase light pollution.